Notation Score as Embodied Documentary Presence: A Response to Amelia Jones's "'Presence' in Absentia" - Kosstrin, Hannah (The International Journal of Screendance, 2019)
No abstract available This article was originally published by Parallel Press, an imprint of the University of Wisconsin-Madison Libraries, as part of The International Journal of Screendance, Volume 2 (2012), Parallel Press. It is made available here with the kind permission of Parallel Press.